2007
DOI: 10.1515/cclm.2007.087
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of ischemia-modified albumin in healthy volunteers after exercise-induced calf-muscle ischemia

Abstract: IMA may represent a clinical marker for skeletal muscle ischemia, although its lack of specificity requires careful clinical interpretation of data. The short period of IMA elevation after ischemic exercise requires standardized conditions for use as a diagnostic tool and hints at IMA applicability as a marker of prolonged or chronic ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The levels of serum IMA were analyzed using the rapid and colorimetric method developed by Bar et al 14 The results were reported as absorbance unit (ABSU). The adjusted IMA levels were calculated with the formula suggested by Lippi et al 15 Albumin-adjusted IMA (AdJ-IMA) levels expressed as individual serum albumin concentration/median albumin concentration of the population x IMA value.…”
Section: Measurement Of Ischemia-modified Albuminmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of serum IMA were analyzed using the rapid and colorimetric method developed by Bar et al 14 The results were reported as absorbance unit (ABSU). The adjusted IMA levels were calculated with the formula suggested by Lippi et al 15 Albumin-adjusted IMA (AdJ-IMA) levels expressed as individual serum albumin concentration/median albumin concentration of the population x IMA value.…”
Section: Measurement Of Ischemia-modified Albuminmentioning
confidence: 99%
“…Serum IMA levels were found to be increased in non-myocardial ischemic conditions such as skeletal muscle ischemia, stroke, and pulmonary thromboembolism. 16,24 The cobalt-binding capacity of albumin reduces, because of oxidative free radicals during ischemia and this new chemically changed albumin can be measured with albumin cobalt binding test. High values of IMA are closely related to ischemia.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of IMA increase in other diseases, such as acute stroke, pulmonary embolus, peripheral artery disease and end-stage renal disease [9,10,11,12,13]. In addition, various other conditions, such as exercise, acidosis, or dehydration, also contribute to elevation of IMA levels [14,15]. In contrast to the investigators supporting IMA as a prognostic factor for future cardiovascular events, several teams [16,17,18]reported that IMA was unable to predict serious cardiac outcomes in the short term in patients with potential acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigations involving IMA and physical activity have focused on the acute effects of exercise, [26][27][28][29] but only one study was found to investigate the chronic effects of exercise training (aerobic) in non-athletes 30 and no studies were found regarding RT and IMA levels. In this matter, three months of moderate-intensity walking unchanged IMA levels in type 2 diabetes mellitus patients, while its levels increased in the sedentary group.…”
Section: Discussionmentioning
confidence: 99%